2020
DOI: 10.1097/md.0000000000021622
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported oral hygiene practices with emphasis on frequency of tooth brushing

Abstract: The objective of the study was to characterize self-reported oral hygiene practices among Mexican older adults aged ≥60 years, and to measure the association between frequency of tooth brushing and a set of sociodemographic, socioeconomic, and dental variables. We conducted a cross-sectional study of 139 older adults aged ≥60 years in Pachuca, Mexico. A questionnaire and a clinical dental examination were administered to identify specific variables. We determined frequency of tooth brushing (or clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
0
7
0
1
Order By: Relevance
“…Poor oral hygiene increases the risk of aspiration pneumonia, and research has shown that suppressing oral microbes through effective oral hygiene is one way to prevent aspiration pneumonia [ 24 ]. However, oral hygiene practices among older adults are poor, and this population typically does not receive oral hygiene instruction to care for their natural teeth or dentures [ 25 ]. At the same time, the ability of older adults to maintain oral health may be diminished by cognitive decline, reduced hand function, sarcopenia, and loss of autonomy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor oral hygiene increases the risk of aspiration pneumonia, and research has shown that suppressing oral microbes through effective oral hygiene is one way to prevent aspiration pneumonia [ 24 ]. However, oral hygiene practices among older adults are poor, and this population typically does not receive oral hygiene instruction to care for their natural teeth or dentures [ 25 ]. At the same time, the ability of older adults to maintain oral health may be diminished by cognitive decline, reduced hand function, sarcopenia, and loss of autonomy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, institutionalized older adults have poor oral hygiene [ 4 , 5 ]. In Mexico, a study of 139 persons ≥ 60 years old found that only 39.3% of residents in a public nursing home reported brushing their teeth at least once a day [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Taiwan among adults aged over 65 demonstrated that having good oral hygiene practices, including regular tooth brushing, was associated with having more remaining teeth [ 38 ]. Oral hygiene practices are essential to prevent oral diseases, keep teeth in the mouth, and maintain good oral health [ 4 , 34 , 36 , 37 ]. Besides, it is necessary to continuously train personnel to perform tasks related to oral care and caries prevention with the use of silver diamine fluoride [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo que las medidas deben estar encaminadas a la reducción del principal agente etiológico en la aparición de las enfermedades bucales, el biofilm. El mantenimiento del equilibrio de la microbiota bucal es la forma más sencilla de prevenir las enfermedades bucales (29), a través de acciones costo efectivas como lo es el cepillado dental (11,(30)(31)(32).…”
Section: Introductionunclassified